The therapeutic effect of N‐acetylcysteine as an add‐on to methadone maintenance therapy medication in outpatients with substance use disorders: A randomized, double‐blind, placebo‐controlled clinical trial - Fateme Padoei; Peyman Mamsharifi; Pooya Hazegh; Homa Boroumand; Fatemeh Ostadmohammady; Samira Abbaszadeh‐Mashkani; Hamid Reza Banafshe; Amir Hassan Matini; Amir Ghaderi; Somayeh Ghadami Dehkohneh (Brain and Behavior, 2023)
Abstract Objective Patients with substance use disorders (SUD) under methadone maintenance therapy (MMT) are susceptible to a number of complications (psychological and metabolic disorders). Evidence studies have shown the roles of the glutamatergic system in addiction. N‐Acetylcysteine (NAC) enhances extracellular glutamate, and is effective in the treatment of neuropsychiatric disorders. We assessed oral NAC as an add‐on to MMT medication for the treatment of SUD. Methods In the current randomized, double‐blind, placebo‐controlled clinical trial, outpatients with SUD under MMT who were 18–60 years old received 2400 mg/day NAC (n = 30) or placebo (n = 30) for 12 weeks. Psychological status and metabolic biomarkers were assessed at baseline and the end of the trial. Results Compared with the placebo group, NAC treatment resulted in a significant improvement in depression score (β −2.36; 95% CI, −3.97, −0.76; p = .005), and anxiety score (β −1.82; 95% CI, −3.19, −0.44; p = .01). Furthermore, NAC treatment resulted in a significant elevation in total antioxidant capacity levels (β 72.28 mmol/L; 95% CI, 11.36, 133.19; p = .02), total glutathione (GSH) levels (β 81.84 μmol/L; 95% CI, 15.40, 148.28; p = .01), and a significant reduction in high‐sensitivity C‐reactive protein levels (β −0.89 mg/L; 95% CI, −1.50, −0.28; p = .005), and homeostasis model of assessment‐insulin resistance (β −0.33; 95% CI, −0.65, −0.009; p = .04), compared with the placebo group. Conclusion In the current study, improvement in depression and anxiety symptoms as well as some metabolic profiles with NAC treatment for 12 weeks in outpatients with SUD under MMT was detected.